2021
DOI: 10.1002/slct.202102033
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Constructed Wetland‐Microbial Fuel Cell using Biochar as Wetland Matrix: Influence on Power Generation and Textile Wastewater Treatment

Abstract: The present study aims at integrating Constructed Wetland using biochar as matrix with Microbial Fuel Cell (CW‐MFC) and evaluating its effect on textile wastewater (TW) treatment in the form of removal of COD, Color and TDS along with Bioelectricity generation. Two vertical down flow systems of CW‐MFC were investigated for TW treatment and system reusability (with and without corn cob biochar) in batch mode with retention time of 10 days for 10 cycles. The performance of CW‐MFC with the corn cob biochar (CW‐MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Compared to these studies, the cathodic region in our research demonstrated better COD removal rates (9.6-18.5%) and decolorization rates (6.1-25.2%), slightly higher than the results of adsorption experiments. The enhancement in decolorization ability of this region may be attributed to the combined adsorption of wetland plants and activated carbon particles in the CW region [28,29]. The effectiveness of COD removal may result from the combined action of activated carbon adsorption and wetland plant degradation in the cathodic region.…”
Section: Electricity Production Performance and Removal Efficiencymentioning
confidence: 99%
“…Compared to these studies, the cathodic region in our research demonstrated better COD removal rates (9.6-18.5%) and decolorization rates (6.1-25.2%), slightly higher than the results of adsorption experiments. The enhancement in decolorization ability of this region may be attributed to the combined adsorption of wetland plants and activated carbon particles in the CW region [28,29]. The effectiveness of COD removal may result from the combined action of activated carbon adsorption and wetland plant degradation in the cathodic region.…”
Section: Electricity Production Performance and Removal Efficiencymentioning
confidence: 99%